Antibacterial Activity Of Hydrogel Plasters Of Red Betel Leaves Extract (Piper Ornatum) And Porang Flour As Gelling Agent Against Staphylococcus Aureus - Husnun Hanifah (Media Farmasi Indonesia, 2025)
Wounds require treatment to prevent infection by covering, one of which is by using a plaster. Hydrogel plaster has flexible, transparent, and soft properties that are non-irritating, providing a soothing and cooling effect. Red betel leaves have germicidal, antioxidant, fungicidal, and antifungal properties and play a role in the wound healing process. The aim of this study was to determine the flavonoid content of red betel extract, physical quality and antibacterial activity of red betel extract hydrogel plaster and porang flour against Staphylococcus aureus bacteria. The type of research used was quantitative research with descriptive design. The method used was spectrophotometry to determine flavonoid levels and the pitting diffusion method for antibacterial activity. Red betel leaves extract has flavonoid content of 14.846 ± 0.17 mg QE/g. Three formulas of hydrogel plaster were made, namely F0, F1 and positive control. The physical quality of the hydrogel plaster includes organoleptic tests on 3 formulas which are in the form of solid preparations, soft and elastic, transparent and dark brown in color, distinctive odor of red betel leaves, pH 4.5-7, thickness 0.630-0.673 mm not more than 1 mm, f olding resistance >200 times, and drying shrinkage of 1.002-1.006% meeting the requirements <9.29%. The antibacterial activity test shows that the hydrogel plaster has antibacterial activity against Staphylococcus aureus bacteria at F0 of 0.00 mm with a very weak inhibition zone category and F1 of 19.47 mm strong category, positive control of 21.43 mm very strong and on red betel extract of 20.5 mm strong category.